News Sources and Consideration in Making Editorial and Commercial Content in the YouTube News Channels - Oktavianti, Roswita; Paramita, Sinta; Sukendro, Gregorius Genep (Jurnal Pekommas, 2022)
YouTube has increasingly gained popularity among news media outlets. Numerous contents have been uploaded on news media official YouTube channels either in the form of regular or commercial news. In Indonesia, two national news media outlets, Kompas.com and Tribunnews.com, which initially focused on publishing their articles on their website, have employed so-called mobile journalists who can primarily produce and edit news videos for YouTube. This study is part of our research on the content industry in a disruptive era with mass media in Indonesia as a subject. This research aims to seek editorial and commercial content sources from mobile journalists and the considerations mobile journalists should make when creating editorial and commercial content for YouTube news channels. To answer these questions, we have identified the trending topics on social media and conducted a content analysis. In addition, we observed Kompas.com and Tribunnews.com YouTube channels and conducted interviews with the news editorial staff. The findings showed that regular news, trending and viral news, unique and in-depth reporting and online events, international news, Q&A with experts based on users' comments, and hot news from other YouTube accounts are the primary news sources for mobile journalists. These are utilized for either business purposes or newsroom agendas. It also discusses what aspects the journalists must consider before producing editorial and commercial content on their YouTube news channels.